The Potential of Periurban Areas for the Resilience of Metropolitan Region. - Colucci, Angela (TeMA - Journal of Land Use, Mobility and Environment, 2015)
The paper aims to present as an organic structure the outcomes from various pieces of research and consulting activities developed over the last few years (2011-2015). Shared topics are: urban-rural partnerships, food planning, metropolitan polices and the territorial resilience of periurban areas. In the first part (the core of the paper) the paper underlines critical questions and establishes needs so as to move towards a new approach to development processes in periurban areas. The paper uses some key concepts to present the main outcomes: 1. Understanding complexity (multiscales in space) and dynamics (multiscales in time); 2. Identifying all the resources and opportunities; 3. Crosscutting and multi-issues. In the second part (in the final part) the paper proposes the “Ecotone” metaphor to support innovation in the approach to periurban areas. It is a “zone of transition between adjacent ecological systems, having a set of characteristics uniquely defined by space and time scales and by the strength of the interactions between adjacent ecological systems” (Hansen et al, 1992). In these terms, periurban areas may be assumed to be ecotonal zones of transition between urban and rural or natural systems. Using the concept of “ecotonal buffer of transition” to approach the periurban systems it is possible to connect main needs and critical questions underlined to a homogeneous framework and to emphasise on the strategic role that the peri-urban systems play for the future development of metropolitan regions oriented to a improvement of resilience of socio-ecosystems. In the final part the paper focuses on the governace of urban rural partnerships and research perspectives.